Pendekatan Restorative Justice oleh Kejaksaan dalam Penyelesaian Perkara Pidana Penganiayaan Anak di Rumah Restorative Justice - Femi Zulfa Nurkheliza; Heni Siswanto; Dona Raisa Monica (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2025)
The Attorney General's Office plays a strategic role as a neutral facilitator that initiates, leads, and oversees the peace process, from peace offers and mediation to the issuance of a suspension of prosecution based on Attorney General Regulation No. 15 of 2020, while still considering the best interests of children, the restoration of social relations, and the legal benefits for all parties. This approach is considered effective in minimizing the traumatic impact of formal judicial proceedings on children while encouraging the social reintegration of perpetrators. However, the implementation of restorative justice still faces internal obstacles, such as limited operational regulations, the understanding and capacity of law enforcement officials, and suboptimal infrastructure. On the other hand, external obstacles arise from low public awareness of the law, a tendency to demand severe punishment, and a culture that emphasizes pride, which hinders the acceptance of peaceful resolutions. This study emphasizes the importance of strengthening regulations, improving the competence of officials, optimizing the function of Restorative Justice Houses, and intensifying public awareness so that the application of restorative justice in cases of child abuse is not only a procedural alternative but truly functions as a fair and sustainable recovery mechanism.